Surface roughness of enamel and four resin composites - Botta, Ana Carolina [UNESP]; Duarte, Sillas; Paulin Filho, Pedro Iris; Gheno, Simoni Maria; Powers, John M. (Mosher & Linder, Inc, 2009)
Purpose: To assess surface roughness of resin composites submitted to different polishing techniques compared to intact human enamel. Methods: Nanofilled (Filtek Supreme XT), microhybrid (Point 4), hybrid (Tetric Ceram), and microfilled (Durafill VS) resin composites were selected. Four polishing techniques were tested (TO: Mylar matrix - control; T1: aluminum oxide discs; T2: felt + diamond paste; T3: aluminum oxide discs + felt + diamond paste) with each resin composite. The specimens were assigned to 16 experimental groups and one control group (n=4). Flat buccal surfaces of four human maxillary central incisors were used for the analysis of enamel roughness and served as control. The mean roughness was evaluated under atomic force microscopy in the contact mode. The obtained data were submitted to Student's t-test, ANOVA, and Tukey's Test, at 0.05 level of significance. Results: The roughness of enamel was 46.6 +/- 10.7 nm. The smoothest surface was obtained for the Mylar matrix with nanofiller (23.6 +/- 3.0 nm), microhybrid (12.8 +/- 1.4 nm), or hybrid resin (15.2 +/- 1.9 nm). Microfilled resin showed the lowest roughness with aluminum oxide discs (43.0 +/- 5.2 nm). Diamond paste increased the roughness of composites, whereas aluminum oxide discs yielded the smoothest surfaces. (Am J Dent 2009;22:252-254).